HOW WOMEN BECOME INTERESTED IN POLITICS - Nanaho Hanada (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2018)
Women are politically underrepresented. This is true in Japan regardless of its political and economic standings suggesting that it is an industrialized democracy. While underrepresented in the political arena, Japanese women are fairly active in non- profit organizations. This paper explores the way in which women can be channeled into politics from civil society through organizational activities, I engaged in semi-structured interviews with 62 women from 41 non-profit organizations. I found that the relationship between organizations and the government was the key. The women in those organizations which have established a partnership with government were provided with the opportunity to enhance their self-efficacy by engaging in competitive selection processes and to dismantle the image of politics being contaminatedand negative by developing a personalized network with government officials and members in other organizations. They come to view their activities as being political and even consider running for office